2021
DOI: 10.1177/20503121211001137
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the coronavirus disease 2019 pandemic on the Palestinian family: A cross-sectional study

Abstract: Introduction: The current study aims to understand and assess the consequences of the coronavirus disease 2019 pandemic on Palestinian families. Methods: This online community-based cross-sectional descriptive study was conducted between 19 April 2020 and 5 June 2020, using a validated questionnaire. The questionnaire comprised of three sections: sociodemographic characteristics, living conditions, and impact of the coronavirus disease 2019 pandemic. A convenience sampling method was used to select participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…Before the pandemic started more than quarter of the Palestinians lived below poverty line, 30% in West Bank and 64% in Gaza, the youth employment rate is 38%. Gender should be involved in any attempt to COVID in Opt (23). Our study showed higher rate of distress than what was reported by other research group in Palestine.…”
Section: Discussioncontrasting
confidence: 48%
“…Before the pandemic started more than quarter of the Palestinians lived below poverty line, 30% in West Bank and 64% in Gaza, the youth employment rate is 38%. Gender should be involved in any attempt to COVID in Opt (23). Our study showed higher rate of distress than what was reported by other research group in Palestine.…”
Section: Discussioncontrasting
confidence: 48%
“… 14 16 These, in addition to many other factors, have deepened the fragility of Gaza’s health system and efforts towards universal health coverage during the COVID-19 pandemic. 17 19 …”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] These, in addition to many other factors, have deepened the fragility of Gaza's health system and efforts towards universal health coverage during the COVID-19 pandemic. [17][18][19] There is broad recognition that the OH approach to health through an improved surveillance system is central to a resilient and sustainable health system. 20 A recent commentary discussed OH principles' contributions in strengthening the global response to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…This cross-sectional study used a snowball sampling technique, the study was employed among different healthcare professionals after discovered cases in Gaza Strip, Palestine, from 5 August to 5 September 2020. A structured online questionnaire ( Supplemental material ) was distributed through a social media platform (Facebook), the most commonly used social media platform in Palestine, 17 to gather information from the study participants.…”
Section: Methodsmentioning
confidence: 99%